A unidirectional water permeable biodegradable composite material and a method for preparing the same

CN122898029APending Publication Date: 2026-10-13原伟杰
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610867023.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

许多合成薄膜在这些严苛条件下容易老化、脆化、破裂,导致其预设的单向导水功能和保水功能过早失效,使用寿命远低于预期

Benefits of technology

[0025]本发明提供的单向透水的可生物降解复合材料及其制备方法与现有技术相比,具有以下有益效果中的至少一项:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898029A_ABST
    Figure CN122898029A_ABST
Patent Text Reader

Abstract

The application belongs to the field of biodegradable composite materials, and relates to a unidirectional water-permeable biodegradable composite material and a preparation method thereof. The method comprises the following steps: dissolving a first biodegradable polymer in a first solvent to obtain slurry A; coating the slurry A into a first wet film and performing directional stretching, removing the first solvent after cooling and solidification to obtain a first layer film; dissolving a second biodegradable polymer with different hydrophilicity from the first biodegradable polymer in a second solvent to obtain slurry B; coating the slurry B on the surface of the first layer film to form a second wet film, then performing directional stretching, and removing the second solvent after cooling and solidification to obtain a composite film with a microporous structure. The application also provides a unidirectional water-permeable biodegradable composite material prepared by the above method. The material can realize selective and efficient permeation of water from one side to the other side, while inhibiting reverse evaporation of water, and meets the core requirements of water collection and water conservation in typical regions such as deserts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biodegradable composite materials, specifically relating to a one-way permeable biodegradable composite material and its preparation method. Background Technology

[0002] In arid and semi-arid regions, especially during desert ecological restoration and vegetation establishment, extreme water scarcity is one of the biggest limiting factors. Studies have found that effective water enrichment and evaporation inhibition in deserts are crucial for improving plant seed germination rates, seedling survival, and subsequent growth.

[0003] Mulching technology is a common technique for suppressing water evaporation in arid regions. Films made from materials with unidirectional hydrophobic properties can trap moisture and inhibit evaporation. These films allow water vapor in the air to condense and be channeled unidirectionally into the lower soil layers for plant use, while simultaneously preventing upward evaporation of deep soil moisture at high temperatures.

[0004] However, most existing unidirectional hydrophilic materials are unsuitable for desert environments. For example, patent CN115139601A discloses a unidirectional hydrophilic composite fiber membrane and its preparation method. First, a hydrophilic material is dissolved in water to obtain a hydrophilic spinning solution; a hydrophobic material is dissolved in a solvent to obtain a hydrophobic spinning solution; then, aluminum foil is used as a receiving device for electrospinning the hydrophilic spinning solution, followed by post-processing to obtain a first fiber membrane; aluminum foil is used as a receiving device for electrospinning the hydrophobic spinning solution, followed by post-processing to obtain a second fiber membrane; finally, the second fiber membrane is placed on top of the first fiber membrane and cold-pressed to obtain a unidirectional hydrophilic composite fiber membrane; or, by adjusting the electrospinning parameters and conditions, the first fiber membrane is used as a receiving device for electrospinning the hydrophobic spinning solution, followed by post-processing to obtain a unidirectional hydrophilic composite fiber membrane. This fiber membrane is used to make moisturizing face mask materials, but its materials are unsuitable for desert environments, and its production is limited by the manufacturing process.

[0005] Current one-way permeable membranes, when applied to desert environments, reveal a series of insurmountable drawbacks. For example, some materials are non-biodegradable; these synthetic materials are extremely stable in the environment and difficult to decompose naturally. After use, they remain for a long time or even break down into microplastics, causing serious white pollution, damaging sand structure, and their physical barrier function may also hinder the later extension of plant roots into deeper soil layers. Some synthetic materials or additives used in their production may have toxic or inhibitory effects on soil microbial communities and plant roots, affecting the restoration of soil microecology and healthy plant growth. Desert soils are generally extremely barren, with very low levels of organic matter and key nutrients. Existing one-way permeable membranes only focus on water regulation and have no ability to improve soil fertility. After their service life, they become difficult-to-manage waste, unable to provide any valuable nutrient supplementation to the barren sandy soil, and unable to achieve the ecological cycle of "turning waste into treasure." In practice, it is often necessary to apply large amounts of fertilizer at the same time as or after laying these membranes, which is not only costly but also difficult to guarantee in windy and sandy environments, and poses a risk of nutrient loss and pollution. In addition, desert environments are characterized by intense ultraviolet radiation, extreme diurnal temperature variations, and frequent wind and sand erosion. Many synthetic films are prone to aging, embrittlement, and cracking under these harsh conditions, causing their intended one-way hydrophobic and water-retention functions to fail prematurely, resulting in a service life far shorter than expected.

[0006] Therefore, how to prepare one-way permeable materials suitable for typical difficult site environments such as deserts and capable of large-scale production has become an urgent problem to be solved in this field. Summary of the Invention

[0007] The purpose of this invention is to solve the problems existing in the prior art and to provide a one-way permeable biodegradable composite material and its preparation method.

[0008] According to one aspect of the present invention, a method for preparing a one-way permeable biodegradable composite material is provided, the method comprising the following steps: Slurry A is prepared by dissolving the first biodegradable polymer in a first solvent; The slurry A is coated into a first wet film, the first wet film is oriented and stretched, and after cooling and curing, the first solvent is removed to obtain a first film with a microporous structure. Slurry B is prepared by dissolving a second biodegradable polymer in a second solvent. The second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer. The slurry B is coated on the surface of the first layer membrane to form a second wet membrane. The first layer membrane and the second wet membrane are then oriented and stretched together. After cooling and curing, the second solvent is removed to obtain a composite membrane with a microporous structure. The composite membrane includes a first layer membrane and a second layer membrane that are tightly bonded together.

[0009] According to one embodiment of the present invention, the first biodegradable polymer and the second biodegradable polymer are each selected from at least one of the following six groups, wherein: Group G1 includes at least one of the following: sodium alginate, alginate, hyaluronic acid, and polyacrylic acid; Group G2 includes at least one of the following: polyvinyl alcohol, polyethylene glycol and its derivatives, polyoxyethylene and its copolymers; Group G3 includes at least one of the following: amino acids, gum arabic, xanthan gum, gelatin, guar gum, starch-based materials and their derivatives, chitosan, cellulose and its derivatives, and proteins; Group G4 includes at least one of the following: lignin and lignin derivatives; Group G5 includes at least one of the following: polylactic acid, polylactic acid-hydroxyacetic acid copolymer, polyhydroxybutyrate, polybutylene succinate, polybutylene succinate, polypropylene glycol succinate, polybutylene adipate, polyhydroxybutyrate-valerate, polycaprolactone, polyhydroxysuccinate, polybutylene sebacate, polybutylene terephthalate, and polypropylene glycol terephthalate. Group G6 includes at least one of the following: polypropylene carbonate, polytrimethylene carbonate.

[0010] According to one embodiment of the present invention, the first biodegradable polymer is a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups; the second biodegradable polymer is a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups; the first biodegradable polymer is selected from at least one of groups G1, G2, and G3, and the second biodegradable polymer is selected from at least one of groups G4, G5, and G6.

[0011] According to one embodiment of the present invention, the first solvent and the second solvent are solvents capable of dissolving the corresponding biodegradable polymer and are selected from at least one of the following components: dichloromethane, chloroform, tetrahydrofuran, acetone, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone, dimethyl sulfoxide, 1,4-dioxane, toluene, xylene, water, ethanol, methanol, isopropanol, n-butanol, tert-butanol, and ethylene glycol.

[0012] According to one embodiment of the present invention, the solid content of slurry A and slurry B is 20% to 80%.

[0013] According to one embodiment of the present invention, the method further includes adding functional fillers to the slurry A and / or the slurry B.

[0014] According to one embodiment of the present invention, the functional filler includes at least one of the following: silica, titanium dioxide, alumina, zinc oxide, montmorillonite, kaolin, hydroxyapatite, iron oxide, zirconium oxide, graphene, zinc oxide, nano-calcium carbonate, carbon nanotubes, water, vitamins, minerals, probiotics, enzymes, pesticides, fertilizer gels, and microcapsules.

[0015] According to one embodiment of the present invention, the amount of the functional filler added is 0.1% to 30% of the mass of the corresponding layer of biodegradable polymer.

[0016] According to one embodiment of the present invention, the method further includes adding a pore-forming agent to the slurry A and / or the slurry B.

[0017] According to one embodiment of the present invention, the pore-forming agent comprises at least one of the following: sodium bicarbonate, ammonium bicarbonate, sodium chloride, potassium chloride, sodium sulfate, ammonium sulfate, sodium nitrate, potassium nitrate, calcium chloride, magnesium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, potassium carbonate, polyvinylpyrrolidone, paraffin wax, urea, oxalic acid, citric acid, and tartaric acid.

[0018] According to one embodiment of the present invention, the amount of pore-forming agent added is 3% to 60% of the mass of the corresponding layer of biodegradable polymer.

[0019] According to one embodiment of the present invention, the directional stretching condition is: The stretching temperature is ±80°C of the melting point of the biodegradable polymer in the wet film; The stretch ratio is 0.5 to 20 times; The stretching method can be uniaxial or biaxial.

[0020] According to one embodiment of the present invention, the method further includes: An additional wet film is coated onto the composite membrane using a slurry made from other biodegradable polymers, which is then oriented and stretched. After cooling and curing, the solvent is removed to form a composite membrane with more layers, wherein the hydrophilicity of each layer of the composite membrane increases or decreases progressively.

[0021] According to an embodiment of the present invention, in step (2), the slurry A is coated on a substrate, the substrate being selected from one of the following materials: glass plate, stainless steel plate, polytetrafluoroethylene plate, polyester film, polypropylene film, polyethylene film, polyimide film, aluminum foil, copper foil, polyvinyl chloride film, polycarbonate plate, acrylic plate, ceramic plate, silicone plate.

[0022] According to one embodiment of the present invention, the coating method is selected from one of the following: doctor blade coating, cast coating, roller coating, dip coating, spray coating, and slot coating.

[0023] According to one embodiment of the present invention, the cooling and curing method is selected from one of the following: air cooling, water cooling, liquid nitrogen cooling or natural cooling, and the cooling temperature is -80°C to 40°C.

[0024] According to another aspect of the present invention, a one-way permeable biodegradable composite material is provided, said composite material being prepared by the method described in any of the above embodiments.

[0025] The one-way permeable biodegradable composite material and its preparation method provided by the present invention have at least one of the following beneficial effects compared with the prior art: (1) This invention uses biodegradable materials as the matrix and adopts a wet pore-forming process. By combining the compatibility characteristics of materials, a microporous membrane material with a gradient hydrophilic and hydrophobic structure and efficient unidirectional hydrophobic properties is prepared. Through the gradient control of the hydrophilicity of the multilayer membrane, the selective and efficient infiltration of water from the air side to the soil side is achieved, while significantly inhibiting the reverse evaporation of soil moisture, thus meeting the core needs of desert water collection and water conservation. (2) The method of the present invention adopts a directional stretching pore-forming process, which significantly simplifies the process steps, reduces the dependence on high-precision equipment, and minimizes or avoids the use of a large amount of organic solvents in the key pore-forming steps, thereby effectively reducing production costs, improving production efficiency, and reducing environmental burden and solvent recovery pressure. (3) The main body of the one-way permeable biodegradable composite material of the present invention is a biodegradable polymer. It can be naturally degraded after use, avoiding the long-term pollution and microplastic problems of traditional plastic films. It has good ecological compatibility. Moreover, the polymer degradation products can be converted into organic matter and plant nutrients, actively improving the structure of barren desert soil, enhancing fertility, and making up for the shortcomings of existing materials that ignore soil barrenness. (4) The biodegradable polymer and composite structure selected in the one-way permeable biodegradable composite material of the present invention provide better structural stability and service life in the strong UV and sandstorm environment of the desert. Attached Figure Description

[0026] Figure 1 A flowchart illustrating a method for preparing a one-way permeable biodegradable composite material according to an embodiment of the present invention is shown; Figure 2 A flowchart illustrating a method for preparing a one-way permeable biodegradable composite material according to another embodiment of the present invention is shown; Figure 3Scanning electron microscope (SEM) images of the composite materials prepared in Examples 1-3 are shown, wherein Figure (a) is an SEM image of the composite material prepared in Example 1, Figure (b) is an SEM image of the composite material prepared in Example 2, and Figure (c) is an SEM image of the composite material prepared in Example 3. Figure 4 The contact angle test diagrams of the composite material prepared according to Example 1 of the present invention are shown, wherein Figure (a) is a contact angle test diagram of the film prepared on the gelatin and chitosan mixture side, and Figure (b) is a contact angle test diagram of the film prepared on the polylactic acid side. Detailed Implementation

[0027] It should be understood that the embodiments of the invention shown in the exemplary embodiments are merely illustrative. Although only a few embodiments have been described in detail in this invention, those skilled in the art will readily recognize that various modifications are possible without substantially departing from the teachings of the invention. Accordingly, all such modifications should be included within the scope of the invention. Other substitutions, modifications, variations, and deletions can be made to the design, operating conditions, and parameters of the following exemplary embodiments without departing from the spirit of the invention.

[0028] According to one aspect of the present invention, a method for preparing a one-way permeable biodegradable composite material is provided. For example... Figure 1 As shown, the method generally includes the following steps: Step 110: Dissolve the first biodegradable polymer in the first solvent to obtain slurry A; Step 120: Coat slurry A into a first wet film, stretch the first wet film in an orientation, remove the first solvent after cooling and curing, and obtain a first film with a microporous structure. Step 130: Dissolve the second biodegradable polymer in a second solvent to obtain slurry B. The second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer. Step 140: The slurry B is coated on the surface of the first membrane to form a second wet membrane. The first membrane and the second wet membrane are then stretched together in an orientation. After cooling and curing, the second solvent is removed to obtain a composite membrane with a microporous structure. The composite membrane includes a tightly bonded first membrane and a second membrane.

[0029] The present invention provides a method for preparing a one-way permeable biodegradable composite material. Using a biodegradable material as a matrix, a wet pore-forming process is employed, combined with the material's compatibility characteristics, to prepare a microporous membrane material with a gradient hydrophilic and hydrophobic structure and efficient one-way hydrophobic properties. By controlling the gradient of the hydrophilicity of the multilayer membrane, selective infiltration of water from the air side to the soil side is achieved, while inhibiting reverse evaporation of soil moisture, thus meeting the core requirements for water collection and retention in deserts.

[0030] When the film prepared by this composite material is applied, the side with stronger hydrophilicity is placed on the side closer to the air, and the side with weaker hydrophilicity is placed on the side closer to the soil. The difference in hydrophilicity between the different layers of the film allows water to selectively and efficiently permeate from the air side to the soil side, while the reverse evaporation of soil moisture is suppressed, achieving a one-way water permeability effect.

[0031] The composite material was prepared using a wet process. After the solvent was removed, some pores were formed in the film, which could serve as channels for water permeation.

[0032] Furthermore, directional stretching of the wet film can form a microporous structure within the film, which serves as a channel for water permeation. By employing a directional stretching pore-forming process, while ensuring that the key microporous structure properties of the resulting material meet application requirements, the process steps are significantly simplified, dependence on high-precision equipment is reduced, and the use of large amounts of organic solvents in the key pore-forming steps is minimized or avoided. This effectively reduces production costs, improves production efficiency, and alleviates environmental burden and solvent recovery pressure.

[0033] The steps of this method are described below as examples.

[0034] In step 110, the first biodegradable polymer is dissolved in a first solvent to obtain slurry A. The first biodegradable polymer is selected from polymeric materials that can degrade in the natural environment.

[0035] It should be noted that the term "dissolved" as used in this invention includes both partial and complete dissolution. In some embodiments, the polymer may be completely dissolved in the solvent to form a true solution. In other embodiments, the polymer may be partially dissolved in the solvent while remaining suspended in the solvent to form a viscous fluid capable of forming a film.

[0036] In some embodiments, the first biodegradable polymer is selected from at least one of the following six groups, wherein: Group G1 includes at least one of the following: sodium alginate, alginate, hyaluronic acid, and polyacrylic acid; Group G2 includes at least one of the following: polyvinyl alcohol, polyethylene glycol and its derivatives, polyoxyethylene and its copolymers; Group G3 includes at least one of the following: amino acids, gum arabic, xanthan gum, gelatin, guar gum, starch-based materials and their derivatives, chitosan, cellulose and its derivatives, and proteins; Group G4 includes at least one of the following: lignin and lignin derivatives; Group G5 includes at least one of the following: polylactic acid, polylactic acid-hydroxyacetic acid copolymer, polyhydroxybutyrate, polybutylene succinate, polybutylene succinate, polypropylene glycol succinate, polybutylene adipate, polyhydroxybutyrate-valerate, polycaprolactone, polyhydroxysuccinate, polybutylene sebacate, polybutylene terephthalate, and polypropylene glycol terephthalate. Group G6 includes at least one of the following: polypropylene carbonate, polytrimethylene carbonate.

[0037] The hydrophilicity of the above components gradually decreases from group G1 to group G6. The polymer used in the same membrane layer can be a single component or a blend of multiple components.

[0038] Using the above components to prepare composite materials not only enables the materials to be biodegradable, but also allows the polymer degradation products to be converted into organic matter and plant nutrients, actively improving the structure of barren desert soils, enhancing fertility, and compensating for the shortcomings of existing materials that ignore soil infertility. Moreover, this material provides superior structural stability and service life in the strong UV and windy sand environment of the desert.

[0039] The first solvent may be a solvent capable of dissolving the first biodegradable polymer, and the first solvent may specifically be selected from at least one of the following components: Dichloromethane, chloroform, tetrahydrofuran, acetone, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone, dimethyl sulfoxide, 1,4-dioxane, toluene, xylene, water, ethanol, methanol, isopropanol, n-butanol, tert-butanol, ethylene glycol.

[0040] The ratio of the first biodegradable polymer to the first solvent results in a solid content of slurry A ranging from 20% to 80%. Within this range, the solid content of slurry A facilitates coating and film formation, and the wet film exhibits toughness and ease of directional stretching. If the solid content of slurry A is below 20%, the slurry is too thin, prone to sagging during coating, difficult to control thickness, and exhibits low mechanical strength after film formation. If the solid content of slurry A is above 80%, the slurry is too viscous, has poor leveling properties, and is difficult to spread evenly. Further, the solid content is 20% to 60%, and even further, it is 40% to 60%.

[0041] In step 120, slurry A is coated into a first wet film, the first wet film is oriented and stretched, and after cooling and curing, the first solvent is removed to obtain a first film with a microporous structure.

[0042] In some embodiments, slurry A is coated onto a smooth substrate that does not react with the slurry. The substrate is selected from one of the following materials: glass plate, stainless steel plate, polytetrafluoroethylene plate, polyester film, polypropylene film, polyethylene film, polyimide film, aluminum foil, copper foil, polyvinyl chloride film, polycarbonate plate, acrylic plate, ceramic plate, and silicone plate.

[0043] In some embodiments, the coating method is any suitable method for film formation of slurry A, such as, but not limited to, blade coating, cast coating, roller coating, dip coating, spray coating, and slot coating.

[0044] In some embodiments, after coating, the first wet film is subjected to directional stretching under the following conditions: The stretching temperature is ±80°C of the melting point of the first biodegradable polymer. If the first biodegradable polymer is a mixture of multiple components, the temperature of the component with the higher melting point shall be used as the reference. The stretch ratio is 0.5 to 20 times, and further, the stretch ratio is 5 to 10 times; The stretching method is uniaxial or biaxial stretching, and the stretching direction is parallel to the plane where the wet film is located.

[0045] The above stretching process can improve the crystallinity and crystal orientation of the polymer, further improving its mechanical properties. At the same time, the stretching process can control the microporous structure of the composite membrane.

[0046] In some embodiments, the first wet film is oriented and stretched before being cooled and cured. Cooling methods include, but are not limited to, air cooling, water cooling, liquid nitrogen cooling, or natural cooling, with cooling temperatures ranging from -80°C to 40°C.

[0047] In some embodiments, the first solvent is removed after curing. The solvent removal method is any suitable method that can effectively separate the solvent, including but not limited to one or more of vacuum distillation, rotary evaporation, natural evaporation, forced air drying, vacuum drying, freeze drying, and extraction.

[0048] This yields a first membrane with a microporous structure, where the pore size can be 0.1~10μm and the porosity can be controlled between 50% and 80%.

[0049] In step 130, a second biodegradable polymer is dissolved in a second solvent to obtain slurry B. The second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer.

[0050] The second biodegradable polymer is selected from polymers that can degrade in the natural environment and whose hydrophilicity differs from that of the first biodegradable polymer. In some embodiments, the second biodegradable polymer is selected from at least one of the following six groups and has a different composition from the first biodegradable polymer, wherein: Group G1 includes at least one of the following: sodium alginate, alginate, hyaluronic acid, and polyacrylic acid; Group G2 includes at least one of the following: polyvinyl alcohol, polyethylene glycol and its derivatives, polyoxyethylene and its copolymers; Group G3 includes at least one of the following: amino acids, gum arabic, xanthan gum, gelatin, guar gum, starch-based materials and their derivatives, chitosan, cellulose and its derivatives, and proteins; Group G4 includes at least one of the following: lignin and lignin derivatives; Group G5 includes at least one of the following: polylactic acid, polylactic acid-hydroxyacetic acid copolymer, polyhydroxybutyrate, polybutylene succinate, polybutylene succinate, polypropylene glycol succinate, polybutylene adipate, polyhydroxybutyrate-valerate, polycaprolactone, polyhydroxysuccinate, polybutylene sebacate, polybutylene terephthalate, and polypropylene glycol terephthalate. Group G6 includes at least one of the following: polypropylene carbonate, polytrimethylene carbonate.

[0051] The polymer used in the same membrane layer can be a single component or a blend of multiple components.

[0052] In some embodiments, the second solvent may be a solvent capable of dissolving the second biodegradable polymer, and the second solvent may specifically be selected from at least one of the following components: Dichloromethane, chloroform, tetrahydrofuran, acetone, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone, dimethyl sulfoxide, 1,4-dioxane, toluene, xylene, water, ethanol, methanol, isopropanol, n-butanol, tert-butanol, ethylene glycol.

[0053] In some embodiments, the second solvent may be the same as or different from the first solvent, depending on the specific components of the first and second biodegradable polymers.

[0054] In some embodiments, the solid content of slurry B is controlled at 20% to 80%, and its solid content may be the same as or different from that of slurry A. Further, the solid content is 20% to 60%, and even further, the solid content is 40% to 60%.

[0055] In one embodiment of the present invention, the first biodegradable polymer may be a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups. The second biodegradable polymer may also be a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups. Furthermore, the different compositions of the first and second biodegradable polymers result in differences in their hydrophilicity. Optionally, the first biodegradable polymer has better hydrophilicity than the second biodegradable polymer. Further, the first biodegradable polymer is selected from groups G1 to G3, while the second biodegradable polymer is selected from groups G4 to G6. This material combination optimizes the unidirectional permeability of the material.

[0056] Because the second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer, a continuous wettability gradient is constructed within the material. Based on capillary effects, water molecules are spontaneously drawn from the more hydrophilic side to the more hydrophobic side, thus achieving unidirectional water transport. Flow in the opposite direction is inhibited because the capillary force is insufficient to drive it.

[0057] In some embodiments, the first biodegradable polymer can be a mixture of polyvinyl alcohol and starch (mass ratio of 10-30:90-70), and the corresponding second biodegradable polymer can be polylactic acid. Optionally, the first biodegradable polymer can be a mixture of gelatin and chitosan (mass ratio of 25-50:75-50), and the corresponding second biodegradable polymer can be polylactic acid. Optionally, the first biodegradable polymer can be polylactic acid, and the corresponding second biodegradable polymer can be a mixture of polypropylene carbonate and polytrimethylene carbonate (mass ratio of 50:50). Optionally, the first biodegradable polymer can be a mixture of sodium alginate and polyacrylic acid (mass ratio of 75-90:25-10), and the corresponding second biodegradable polymer can be chitosan. Optionally, the first biodegradable polymer can be a mixture of polyvinyl alcohol, polyethylene glycol, and polyoxyethylene (mass ratio of 10:10:80), and the corresponding second biodegradable polymer can be polytrimethylene carbonate.

[0058] In step 140, slurry B is coated on the surface of the first membrane to form a second wet membrane. The first membrane and the second wet membrane are then oriented and stretched together. After cooling and curing, the second solvent is removed to obtain a composite membrane with a microporous structure.

[0059] In some embodiments, the coating method of slurry B is any suitable method for film formation of slurry B, such as, but not limited to, blade coating, cast coating, roller coating, dip coating, spray coating, slot coating.

[0060] In some embodiments, after coating, the two films are oriented and stretched together under the following conditions: The stretching temperature is ±80°C of the melting point of the second biodegradable polymer. If the second biodegradable polymer is a mixture of multiple components, the temperature of the component with the higher melting point shall be used as the reference. The stretch ratio is 0.5 to 20 times; The stretching method can be uniaxial or biaxial, with the stretching direction parallel to the plane of the wet film, and can be the same as or different from the stretching direction of the first wet film. Oriented stretching of the two films together can improve the affinity and bonding strength at the interfaces between different layers.

[0061] In some embodiments, the two films are oriented and stretched before being cooled and cured. Cooling methods include, but are not limited to, air cooling, water cooling, liquid nitrogen cooling, or natural cooling, with cooling temperatures ranging from -80°C to 40°C.

[0062] In some embodiments, the second solvent is removed after curing. The solvent removal method is any suitable method that can effectively separate the solvent, including but not limited to one or more of vacuum distillation, rotary evaporation, natural evaporation, forced-air drying, vacuum drying, freeze drying, and extraction.

[0063] The composite membrane consists of a first membrane layer and a second membrane layer that are tightly bonded together. The pore size of the second membrane layer can be 0.1~10μm, and the porosity is controlled between 50% and 80%.

[0064] Optionally, in some embodiments, functional fillers may be added to slurry A and / or slurry B. The main function of these functional fillers is to enhance the mechanical properties of the composite material, regulate its degradation performance, and impart antibacterial, insecticidal, and fertilizer-enhancing effects. The functional fillers include at least one of the following: silica, titanium dioxide, alumina, zinc oxide, montmorillonite, kaolin, hydroxyapatite, iron oxide, zirconium oxide, graphene, zinc oxide, nano-calcium carbonate, carbon nanotubes, water, vitamins, minerals, probiotics, enzymes, pesticides, fertilizer gels, or microcapsules. The amount of functional filler added is 0.1% to 30% of the mass of the corresponding biodegradable polymer layer, and it can be added alone, in combination, or in a gradient distribution.

[0065] Optionally, in some embodiments, a pore-forming agent may be added to slurry A and / or slurry B. The pore-forming agent may include at least one of the following: sodium bicarbonate, ammonium bicarbonate, sodium chloride, potassium chloride, sodium sulfate, ammonium sulfate, sodium nitrate, potassium nitrate, calcium chloride, magnesium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, potassium carbonate, polyvinylpyrrolidone, paraffin wax, urea, oxalic acid, citric acid, and tartaric acid, added in an amount of 3% to 60% of the mass of the corresponding biodegradable polymer. It may be used alone or in combination, and the type and proportion added to each layer may vary. The pore-forming agent can form more pores of controllable size in the membrane.

[0066] Optionally, in some embodiments of the present invention, a method for preparing a composite material having more layers is also involved. For example... Figure 2 As shown, the method includes: Step 210: Dissolve the first biodegradable polymer in the first solvent to obtain slurry A; Step 220: Coat slurry A into a first wet film, stretch the first wet film in an orientation, remove the first solvent after cooling and curing, and obtain a first film with a microporous structure. Step 230: Dissolve the second biodegradable polymer in a second solvent to obtain slurry B. The second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer. Step 240: The slurry B is coated on the surface of the first membrane to form a second wet membrane. The first membrane and the second wet membrane are then stretched together in an orientation. After cooling and curing, the second solvent is removed to obtain a two-layer composite membrane with a microporous structure. Step 250: Repeat steps 230 and 240 multiple times using a different biodegradable polymer than the first and second biodegradable polymers to form a composite membrane with more layers, wherein the hydrophilicity of each layer of the composite membrane increases or decreases layer by layer.

[0067] Based on the design requirements for unidirectional permeability, different formulations of slurry are sequentially coated onto the surface of the formed membrane layers. Functional fillers and pore-forming agents are selectively added to each layer, and directional stretching is performed as needed, ultimately forming a multi-layer composite structure. This achieves precise control over the unidirectional permeability of the composite membrane. This multi-layer composite membrane can include a third, fourth, or even more membrane layers. Composite membranes with more layers offer advantages such as improved mechanical properties and precise control over unidirectional permeability.

[0068] In a multilayered composite membrane, the hydrophilicity of each layer increases or decreases progressively. This means that the hydrophilicity of the first, second, third, and so on layers gradually increases or decreases. In other words, the hydrophilicity of the multilayered membrane changes in an ordered gradient along a single direction.

[0069] In one embodiment of the present invention, when the membrane structure comprises two or more layers, the first biodegradable polymer may be a mixture of polyvinyl alcohol and starch (mass ratio of 10:90), the corresponding second biodegradable polymer may be polylactic acid, and the corresponding third biodegradable polymer may be a mixture of polybutylene succinate and polycaprolactone (mass ratio of 30:70). Optionally, the first biodegradable polymer may be a mixture of sodium alginate and polyacrylic acid (mass ratio of 90:10), the corresponding second biodegradable polymer may be chitosan, the corresponding third biodegradable polymer may be a mixture of polybutylene adipate and polybutylene succinate (mass ratio of 60:40), and the corresponding fourth biodegradable polymer may be polypropylene carbonate.

[0070] The present invention also provides a one-way permeable biodegradable composite material, which is prepared by means of the method described in any of the above embodiments.

[0071] This invention also provides an application of a one-way permeable biodegradable composite material, which is prepared according to the method described in any of the above embodiments. When using this composite material, the side with stronger hydrophilicity is placed closer to the air, and the side with weaker hydrophilicity is placed closer to the soil. The difference in hydrophilicity between the different membrane layers allows for selective and efficient permeation of water from the air side to the soil side, while suppressing reverse evaporation of soil moisture, thus achieving a one-way permeability effect.

[0072] To provide a clearer and more detailed description of the one-way permeable biodegradable composite material and its preparation method provided in the embodiments of the present invention, the following description will be based on specific embodiments.

[0073] Example 1 A mixture of gelatin and chitosan (mass ratio 1:2) was added to an aqueous solution, with a solid content of 20%, and stirred at 50°C until a homogeneous first slurry was formed. This slurry was then coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was employed at approximately 50°C, with a stretching ratio of 0.5 times. After air-cooling curing, the solvent was removed using a forced-air drying method, resulting in a first film with a specific microporous structure.

[0074] Polylactic acid was added to chloroform, with a solid content of 30%, and stirred at 50°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (perpendicular to the x-axis and parallel to the y-axis of the substrate) was then employed, with a stretching temperature of 150°C and a stretching ratio of 4 times. After air-cooling curing and drying, a second film tightly bonded to the first film was formed.

[0075] like Figure 3 As shown in Figure (a), the first layer of the prepared unidirectional permeable membrane has a pore size of 0.5~1μm, and the pores are uniform and three-dimensional. Figure 3 As shown in Figure (d), the second membrane layer has a pore size of 0.3–0.8 μm, and the porosity of the unidirectional permeable membrane is 63%. Figure 4 As shown in Figure (a), the contact angle of the first membrane layer is 68.9°. Figure 4 As shown in Figure (b), the contact angle of the second membrane is 108.6°. The water vapor transmission rates of the first and second membranes are 305 g / m³, respectively. 2 ·day and 1150g / m 2 The ·day indicates good one-way permeability, and the prepared biodegradable polymer degrades completely in the soil within 180 days.

[0076] Example 2 The process of this embodiment is basically the same as that of embodiment 1, except that the mass ratio of gelatin to chitosan used in the preparation of the first membrane is 1:1.

[0077] like Figure 3 As shown in Figure (b), the first layer of the prepared unidirectional water-permeable membrane has a pore size of 1~2 μm, and the pores are distributed in a layered manner. Figure 3 As shown in Figure (d), the pore size of the second membrane layer is 0.3–0.8 μm, and the porosity of the unidirectional permeable membrane is 60%. The contact angle of the first membrane layer is 70.2°, and the contact angle of the second membrane layer is 108.6°. The water vapor permeability of the first and second membrane layers is 310 g / m³, respectively. 2 ·day and 1027g / m 2 The day indicates that the one-way permeability is slightly lower than that of Example 1, and the prepared biodegradable polymer degrades completely in the soil in 180 days.

[0078] Example 3 The process of this embodiment is basically the same as that of Embodiment 1, except that the mass ratio of gelatin to chitosan used in the preparation of the first membrane is 1:3.

[0079] like Figure 3 As shown in Figure (c), the first layer of the prepared unidirectional water-permeable membrane has a pore size of approximately 1 μm, but the pores are few and unevenly distributed. Figure 3 As shown in Figure (d), the pore size of the second membrane layer is 0.3–0.8 μm, and the porosity of the unidirectional permeable membrane is 57%. The contact angle of the first membrane layer is 74.3°, and the contact angle of the second membrane layer is 108.7°. The water vapor permeability of the first and second membrane layers is 345 g / m³, respectively. 2 ·day and 1021g / m 2 The day indicates that the unidirectional permeability is good and lower than that of Examples 1 and 2, and the prepared biodegradable polymer degrades completely in the soil in 180 days.

[0080] Example 4 A mixture of polyvinyl alcohol and starch (mass ratio 10:90) was added to an aqueous solution, with a solid content of 20%, and stirred at 50°C until a homogeneous first slurry was formed. This slurry was then coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was employed at approximately 50°C with a stretching ratio of 0.5 times. After air-cooling curing, the solvent was removed by forced-air drying, resulting in a first film with a specific microporous structure.

[0081] Polylactic acid was added to chloroform, with a solid content of 30%, and stirred at 50°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (perpendicular to the x-axis and parallel to the y-axis of the substrate) was then employed, with a stretching temperature of 150°C and a stretching ratio of 4 times. After air-cooling curing and drying, a second film tightly bonded to the first film was formed.

[0082] The prepared one-way permeable membrane has a first layer pore size of 1-2 μm and a second layer pore size of 0.5-1 μm. The porosity of the one-way permeable membrane is 63%. The contact angles of the first and second layers are 30° and 90°, respectively. The water vapor permeability of the first and second layers is 310 g / m³. 2 ·day and 1130g / m 2 The ·day indicates good one-way permeability, and the prepared biodegradable polymer degrades completely in the soil within 180 days.

[0083] Example 5 A mixture of polyvinyl alcohol and starch (mass ratio 20:80) was added to an aqueous solution, with a solid content of 40%, and stirred at 40°C until a homogeneous first slurry was formed. This slurry was then coated onto a stainless steel plate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was employed at approximately 60°C with a stretching ratio of 5. After water-cooling curing, the solvent was removed by rotary evaporation, and the film was dried to obtain a first membrane with a specific microporous structure.

[0084] Polylactic acid was added to chloroform, with a solid content of 50%, and stirred at 50°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (y-axis) was employed, with a stretching temperature of 160°C and a stretching ratio of 6 times. After air cooling, curing, and drying, a second film tightly bonded to the first film was formed.

[0085] The first layer of the prepared one-way permeable membrane has a pore size of 0.8~1.5μm, and the second layer has a pore size of 0.6~1.2μm. The porosity of the one-way permeable membrane is 65%. The contact angles of the first and second layers are 35° and 95°, respectively. The water vapor permeability of the first and second layers is 318g / m²·day and 1150g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer is completely degraded in the soil within 180 days.

[0086] Example 6 A mixture of polyvinyl alcohol and starch (mass ratio 30:70) was added to an aqueous solution, with a solid content of 50%, and stirred at 40°C until a homogeneous first slurry was formed. This slurry was then coated onto a stainless steel plate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was employed at approximately 70°C with a stretching ratio of 8 times. After water-cooling curing, the solvent was removed using vacuum drying, resulting in a first film with a specific microporous structure.

[0087] A mixture of polybutylene succinate and polycaprolactone (mass ratio 50:50) was added to dichloromethane, with a solid content of 50%, and stirred at 60°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (y-axis) was employed at a stretching temperature of 70°C and a stretch ratio of 10 times. After air-cooling and curing, a second film tightly bonded to the first film was formed.

[0088] The first layer of the prepared one-way permeable membrane has a pore size of 1.8~2.5μm, and the second layer has a pore size of 2.3~3.2μm. The porosity of the one-way permeable membrane is 69%. The contact angles of the first and second layers are 70° and 84°, respectively. The water vapor permeability of the first and second layers is 415g / m²·day and 1523g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer degrades to 95% in the soil after 180 days.

[0089] Example 7 A mixture of sodium alginate and polyacrylic acid (mass ratio 75:25) was added to a water-ethanol solution, with a solid content of 60%, and stirred at 25°C until a homogeneous first slurry was formed. This slurry was then coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (y-axis) was employed at approximately 90°C with a stretching ratio of 10 times. After cooling and curing, the solvent was removed using a forced-air drying method, resulting in a first film with a specific microporous structure.

[0090] A mixture of polybutylene succinate and polycaprolactone (mass ratio 50:50) was added to dichloromethane, with a solid content of 60%, and stirred at 60°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (x-axis) was employed at 80°C with a stretching ratio of 15 times. After cooling and curing, the solvent was removed by extraction, and the film was dried to form a second film tightly bonded to the first film.

[0091] The first layer of the prepared one-way permeable membrane has a pore size of 0.2~0.3μm, and the second layer has a pore size of 1.5~2.3μm. The porosity of the one-way permeable membrane is 67%. The contact angles of the first and second layers are 23° and 85°, respectively. The water vapor permeability of the first and second layers is 140g / m²·day and 1810g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer is completely degraded in the soil within 180 days.

[0092] Example 8 A mixture of sodium alginate and polyacrylic acid (mass ratio 85:15) was added to a water-ethanol solution, with a solid content of 80%, and stirred at 25°C until a homogeneous first slurry was formed. This slurry was then coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (y-axis) was employed at approximately 100°C with a stretching ratio of 20 times. After cooling and curing, the solvent was removed using a forced-air drying method, resulting in a first film with a specific microporous structure.

[0093] Polytrimethylene carbonate was added to dichloromethane, with a solid content of 80%, and stirred at 30°C until a homogeneous second slurry was formed. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (x-axis) was employed at a stretching temperature of 50°C and a stretching ratio of 20 times. After cooling and curing, the solvent was removed by extraction, and after drying, a second film tightly bonded to the first film was formed.

[0094] The first layer of the prepared one-way permeable membrane has a pore size of 0.8~1.3μm, and the second layer has a pore size of 0.5~1.2μm. The porosity of the one-way permeable membrane is 67%. The contact angles of the first and second layers are 35° and 105°, respectively. The water vapor permeability of the first and second layers is 150g / m²·day and 1830g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer is completely degraded in the soil within 180 days.

[0095] Example 9 A mixture of polyvinyl alcohol and starch (mass ratio 10:90) was added to an aqueous solution (solid content 35%) and stirred at 50°C until a homogeneous slurry was formed. Titanium dioxide (20% of the total mass of polyvinyl alcohol and starch) was added as a functional filler, and stirring continued to form a homogeneous first slurry. This slurry was then coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was employed at approximately 50°C with a stretching ratio of 2. After cooling and curing, the solvent was removed using a forced-air drying method, resulting in a first film with a specific microporous structure.

[0096] Polylactic acid (PLA) was added to chloroform, with a solid content of 30%. The mixture was stirred at 50°C until a homogeneous slurry was formed. Then, functional filler titanium dioxide (20% of the PLA mass) and pore-forming agent sodium carbonate (3% of the PLA mass) were added, and stirring continued to form a homogeneous second slurry. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (y-axis) was employed at 150°C with a stretching ratio of 4 times. After cooling and curing, the solvent and pore-forming agent were removed by extraction. After drying, a second film tightly bonded to the first film was formed.

[0097] A mixture of polybutylene succinate and polycaprolactone (mass ratio 30:70) was added to dichloromethane (solid content 50%) and stirred at 50°C until a homogeneous slurry was formed. This slurry was then spray-coated onto the non-first layer contact surface of the second layer membrane. A biaxial stretching process (x, y axes) was used at a stretching temperature of 100°C and a stretching ratio of 10 times. After cooling and curing, the solvent was removed by freeze-drying, resulting in a third layer membrane tightly bonded to the second layer membrane.

[0098] The prepared one-way permeable membrane has a pore size of 2.1~2.5μm for the first layer, 2.8~3.0μm for the second layer, and 2.0~2.4μm for the third layer. The porosity of the one-way permeable membrane is 69%. The contact angles of the first and third layers are 73° and 85°, respectively. The water vapor permeability of the first and third layers is 440g / m²·day and 1821g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer degrades to 90% in the soil after 180 days.

[0099] Example 10 A mixture of sodium alginate and polyacrylic acid (mass ratio 90:10) was added to a water-ethanol solution, with a solid content of 80%, and stirred at 25°C until a homogeneous slurry was formed. Functional filler graphene and fertilizer microcapsules (30% of the total mass of sodium alginate and polyacrylic acid) were added, and stirring continued to form a homogeneous first slurry. This slurry was then coated onto a glass substrate using a casting method to form a wet film. A uniaxial stretching process (y-axis) was employed at a stretching temperature of approximately 70°C and a stretching ratio of 1.2 times. After cooling and curing, the solvent was removed by freeze-drying, resulting in a first film with a specific microporous structure.

[0100] Chitosan was added to an aqueous solution (70% solids content) and stirred at 50°C until a homogeneous slurry was formed. Functional filler carbon nanotubes (0.1% of the chitosan mass) were then added, and stirring continued to form a homogeneous second slurry. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A uniaxial stretching process (x-axis) was employed at 90°C with a stretching ratio of 3 times. After cooling and curing, the solvent was removed by extraction, and after drying, a second film tightly bonded to the first film was formed.

[0101] A mixture of polybutylene adipate and polybutylene succinate (mass ratio 60:40) was added to tetrahydrofuran (solid content 20%) and stirred at 60°C until a homogeneous slurry was formed. This slurry was then applied to the non-first layer contact surface of the second membrane using a slot coating method. A biaxial stretching process (x, y axes) was employed at a stretching temperature of 100°C and a stretching ratio of 0.5 times. After cooling and curing, the solvent was removed by extraction, and the membrane was dried to form a third layer tightly bonded to the second membrane.

[0102] Polypropylene carbonate (70% solids content) was added to tetrahydrofuran and stirred at 80°C until a homogeneous slurry was formed. This slurry was then spray-coated onto the non-secondary membrane contact surface of the third membrane using a biaxial stretching process (x, y axes) at 80°C with a stretching ratio of 5. After cooling and curing, the solvent was removed by forced-air drying, resulting in a fourth membrane tightly bonded to the third membrane.

[0103] The prepared one-way permeable membrane has a pore size of 0.1~0.3μm for the first layer, 0.2~0.4μm for the second layer, 1.0~1.3μm for the third layer, and 2.5~3.0μm for the fourth layer. The porosity of the one-way permeable membrane is 55%. The contact angles of the first and fourth layers are 23° and 103°, respectively. The water vapor permeability of the first and fourth layers is 130g / m²·day and 2218g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer degrades to 82% in the soil after 180 days.

[0104] Example 11 Polyethylene glycol (PEG) was added to an aqueous solution (80% solids content) and stirred at 30°C until a homogeneous slurry was formed. Functional filler kaolin and pesticide microcapsules (30% of PEG by mass) and pore-forming agent sodium chloride (60% of PEG by mass) were added, and stirring continued to form a homogeneous first slurry. This slurry was coated onto a glass substrate using a doctor blade to form a wet film. A biaxial (x, y axis) stretching process was employed at approximately 50°C with a stretching ratio of 20 times. After cooling and curing, the solvent and pore-forming agent were removed by extraction. After drying, a first membrane with a specific microporous structure was obtained.

[0105] A mixture of polypropylene carbonate and polytrimethylene carbonate (mass ratio 2:1) was added to dichloromethane (solid content 20%) and stirred at 70°C until a homogeneous slurry was formed. This slurry was then applied to the non-substrate contact surface of the first film using a roller coating method. A biaxial (x, y axis) stretching process was employed at a stretching temperature of approximately 50°C and a stretching ratio of 1.5 times. After cooling and curing, the solvent was removed by natural evaporation. After drying, a second film tightly bonded to the first film was formed.

[0106] The first layer of the prepared one-way permeable membrane has a pore size of 2.5~3.0μm, and the second layer has a pore size of 0.7~1.5μm. The porosity of the one-way permeable membrane is 77%. The contact angles of the first and second layers are 63° and 101°, respectively. The water vapor permeability of the first and second layers is 530g / m²·day and 1710g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer degrades to 70% in the soil after 180 days.

[0107] Example 12 A mixture of polyvinyl alcohol, polyethylene glycol, and polyoxyethylene (mass ratio 10:10:80) was added to a mixed solution of chloroform and cyclohexanone (solid content 20%), and stirred at 70°C until a homogeneous slurry was formed. Functional fillers kaolin, montmorillonite, and pesticide microcapsules (20% of the total polymer mass) and a mixture of pore-forming agents ammonium bicarbonate and urea (40% of the total polymer mass) were added, and stirring continued to form a homogeneous first slurry. This slurry was coated onto a glass substrate using a doctor blade to form a wet film. A uniaxial stretching process (x-axis) was used at approximately 80°C with a stretching ratio of 0.5 times. After cooling and curing, the solvent was removed by forced-air drying, resulting in a first film with a specific microporous structure.

[0108] Polytrimethylene carbonate (PTC) was added to dichloromethane (50% solids content) and stirred at 20°C until a homogeneous slurry was formed. A mixture of functional filler vitamin gel and pesticide microcapsules (20% of the PTC mass) and pore-forming agent ammonium bicarbonate (20% of the PTC mass) were then added, and stirring continued to form a homogeneous second slurry. This slurry was then coated onto the non-substrate contact surface of the first film using a roller coating method. A biaxial stretching process (x, y axes) was employed at a stretching temperature of 110°C and a stretching ratio of 0.5 times. After cooling and curing, the solvent and pore-forming agent were removed by extraction. After drying, a second film tightly bonded to the first film was formed.

[0109] The first layer of the prepared one-way permeable membrane has a pore size of 0.3~0.4μm, and the second layer has a pore size of 0.5~0.6μm. The porosity of the one-way permeable membrane is 69%. The contact angles of the first and second layers are 23° and 107°, respectively. The water vapor permeability of the first and second layers is 130g / m²·day and 1831g / m²·day, respectively, indicating good one-way permeability. The prepared biodegradable polymer degrades to 77% in the soil after 180 days.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. Any modifications or equivalent substitutions made to the present invention without departing from the spirit and scope thereof should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a one-way permeable biodegradable composite material, characterized in that, Includes the following steps: Slurry A is prepared by dissolving the first biodegradable polymer in a first solvent; The slurry A is coated into a first wet film, the first wet film is oriented and stretched, and after cooling and curing, the first solvent is removed to obtain a first film with a microporous structure. Slurry B is prepared by dissolving a second biodegradable polymer in a second solvent. The second biodegradable polymer has a different hydrophilicity than the first biodegradable polymer. The slurry B is coated on the surface of the first layer membrane to form a second wet membrane. The first layer membrane and the second wet membrane are then oriented and stretched together. After cooling and curing, the second solvent is removed to obtain a composite membrane with a microporous structure. The composite membrane includes a first layer membrane and a second layer membrane that are tightly bonded together.

2. The method for preparing the unidirectional permeable biodegradable composite material according to claim 1, characterized in that, The first biodegradable polymer and the second biodegradable polymer are each selected from at least one of the following six groups, wherein: Group G1 includes at least one of the following: sodium alginate, alginate, hyaluronic acid, and polyacrylic acid; Group G2 includes at least one of the following: polyvinyl alcohol, polyethylene glycol and its derivatives, polyoxyethylene and its copolymers; Group G3 includes at least one of the following: amino acids, gum arabic, xanthan gum, gelatin, guar gum, starch-based materials and their derivatives, chitosan, cellulose and its derivatives, and proteins; Group G4 includes at least one of the following: lignin and lignin derivatives; Group G5 includes at least one of the following: polylactic acid, polylactic acid-hydroxyacetic acid copolymer, polyhydroxybutyrate, polybutylene succinate, polybutylene succinate, polypropylene glycol succinate, polybutylene adipate, polyhydroxybutyrate-valerate, polycaprolactone, polyhydroxysuccinate, polybutylene sebacate, polybutylene terephthalate, and polypropylene glycol terephthalate. Group G6 includes at least one of the following: polypropylene carbonate, polytrimethylene carbonate.

3. The method for preparing the unidirectional permeable biodegradable composite material according to claim 2, characterized in that, The first biodegradable polymer is a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups; the second biodegradable polymer is a single component, a blend of multiple components from the same group, or a blend of multiple components from different groups; the first biodegradable polymer is selected from at least one of groups G1, G2, and G3, and the second biodegradable polymer is selected from at least one of groups G4, G5, and G6.

4. The method for preparing the unidirectional permeable biodegradable composite material according to claim 1, characterized in that, The first solvent and the second solvent are solvents capable of dissolving the corresponding biodegradable polymers and are selected from at least one of the following components: dichloromethane, chloroform, tetrahydrofuran, acetone, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone, dimethyl sulfoxide, 1,4-dioxane, toluene, xylene, water, ethanol, methanol, isopropanol, n-butanol, tert-butanol, ethylene glycol; and / or The solid content of slurry A and slurry B is 20%~80%.

5. The method for preparing the unidirectional permeable biodegradable composite material according to claim 1, characterized in that, The method further includes adding functional fillers to slurry A and / or slurry B. The functional filler comprises at least one of the following: silica, titanium dioxide, alumina, zinc oxide, montmorillonite, kaolin, hydroxyapatite, iron oxide, zirconium oxide, graphene, zinc oxide, nano-calcium carbonate, carbon nanotubes, water, vitamins, minerals, probiotics, enzymes, pesticides, fertilizer gels, microcapsules; and / or The amount of the functional filler added is 0.1% to 30% of the mass of the biodegradable polymer in the corresponding layer.

6. The method for preparing the one-way permeable biodegradable composite material according to claim 1, characterized in that, The method further includes adding a pore-forming agent to the slurry A and / or the slurry B, wherein: The pore-forming agent comprises at least one of the following: sodium bicarbonate, ammonium bicarbonate, sodium chloride, potassium chloride, sodium sulfate, ammonium sulfate, sodium nitrate, potassium nitrate, calcium chloride, magnesium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, potassium carbonate, polyvinylpyrrolidone, paraffin wax, urea, oxalic acid, citric acid, tartaric acid; and / or The amount of the pore-forming agent added is 3% to 60% of the mass of the corresponding layer of biodegradable polymer.

7. The method for preparing the unidirectional permeable biodegradable composite material according to claim 1, characterized in that, The directional stretching conditions between the first wet film and / or the first layer film and the second wet film are as follows: The stretching temperature is ±80°C of the melting point of the biodegradable polymer in the wet film; The stretch ratio is 0.5 to 20 times; The stretching method can be uniaxial or biaxial.

8. The method for preparing the one-way permeable biodegradable composite material according to claim 1, characterized in that, The method further includes: An additional wet film is coated onto the composite membrane using a slurry made from other biodegradable polymers, which is then oriented and stretched. After cooling and curing, the solvent is removed to form a composite membrane with more layers, wherein the hydrophilicity of each layer of the composite membrane increases or decreases progressively.

9. The method for preparing the one-way permeable biodegradable composite material according to claim 1, characterized in that, The slurry A is coated onto a substrate selected from one of the following materials: glass plate, stainless steel plate, polytetrafluoroethylene plate, polyester film, polypropylene film, polyethylene film, polyimide film, aluminum foil, copper foil, polyvinyl chloride film, polycarbonate plate, acrylic plate, ceramic plate, silicone plate; and / or The coating method is selected from one of the following: blade coating, cast coating, roller coating, dip coating, spray coating, slot coating; and / or The cooling and curing method is selected from one of the following: air cooling, water cooling, liquid nitrogen cooling or natural cooling, with a cooling temperature of -80℃ to 40℃.

10. A one-way permeable biodegradable composite material, characterized in that, The composite material is prepared by the method according to any one of claims 1-9.

Citation Information

Patent Citations

  • One-way water guide composite fiber membrane and preparation method thereof

    CN115139601A